Prevention of uterine adhesion formation following caesarean section in bovines - DHINDSA, S S; DHALIWAL, G P S; GHUMAN, S P S (The Indian Journal of Animal Sciences, 2010)
The present study was planned in 41 dystocia affected bovines to assess the comparative efficacy of natural (chromic catgut, CC) or synthetic (polyglycolic acid, PGA) absorbable suture material used for uterine incision, with or without intra-peritoneal infusion of sodium carboxy methyl cellulose (SCMC 1% @ 14 ml/kg) during caesarean for preventing the post-operative formation of uterine adhesions. All the animals were evaluated for the presence of uterine adhesions either between 30–40 days post-caesarean or at the time of post-mortem if the animal died during the course of study. The animals were divided into groups, viz. 1a (CC, n=9), 1b (CC+SCMC, n=10), 1c (PGA, n=10) and 1d (PGA+SCMC, n=12). All the animals of group 1a exhibited severe degree of uterine adhesions whereas percentage of animals exhibiting severe uterine adhesions were less in group 1d compared to group 1a and 1b. Depending upon the time elapsed between the occurrence and relieving of the dystocia through caesarean section, animals were divided into groups, viz. 2a (<12h, n=12), 2b (12–36h, n=11) and 2c (>36h, n=18). Majority of the animals in group 2a either had no development of uterine adhesions or were not of severe degree in comparison to group 2c. In conclusion, formation of uterine adhesions could be prevented by the use of PGA, instead of CC, for suturing uterine incision along with intra-peritoneal infusion of SCMC during caesarean. Moreover, caesarean section should be performed preferably within 12 h of occurrence of dystocia to reduce the severity of post-caesarean uterine adhesions.